1-Acetyl-6-bromo-1H-imidazo[4,5-b]pyridin-2(3H)-one - Siham Dahmani; Youssef Kandri Rodi; Santiago V. Luis; El Mokhtar Essassi; Lahcen El Ammari (Acta Crystallographica Section E, 2011)
The two fused five- and six-membered rings in the molecule of the title compound, C8H6BrN3O2, are approximately coplanar, the largest deviation from the mean plane being 0.011 (3) Å at the NH atom. The acetyl group is slightly twisted with respect to the imidazo[4,5-b]pyridine system, making a dihedral angle of 2.7 (2)°. In the crystal, adjacent molecules are linked by intermolecular N—H...N and C—H...O hydrogen bonds, forming infinite chains.